Seven Years of Selective Genetic Screening Program and Follow-Up of Asymptomatic Carriers With Hereditary Transthyretin Amyloidosis in Bulgaria - Chamova, Teodora; Gospodinova, Mariana; Asenov, Ognian; Todorov, Tihomir; Pavlova, Zornitsa; Kirov, Andrey; Cherninkova, Sylvia; Kastreva, Kristina; Taneva, Ani; Blagoeva, Stanislava; Zhelyazkova, Sashka; Antimov, Plamen; et al. (Frontiers in Neurology, 2022)
Hereditary transthyretin amyloidosis (ATTRv amyloidosis) is a rare, autosomal-dominant (AD) multisystem disorder resulting from the extracellular deposition of amyloid fibrils formed by a destabilized mutant form of transthyretin (TTR), a transport protein predominantly produced by the liver. Aim The aims of the current study are to demonstrate the Bulgarian experience with the screening programs among the high-risk patient population over the last 7 years, to present the results from the therapy with TTR stabilizer in our cohort, as well as to stress on the importance of a follow-up of asymptomatic carriers with TTR pathogenic variants by a multidisciplinary team of specialists. Materials and Methods In 2014, a screening program among the high-risk patient population for ATTRv was initiated in Bulgaria. On one hand, it was conducted to identify new patients and families among people with “red flag” clinical features, while on the other hand, the program aimed to identify TTR mutation carriers among the families with already genetically proven diagnoses. Sanger sequencing methodology was used to make fast target testing for mutations in the TTR gene in the suspected individuals. All of the identified carriers underwent subsequent evaluation for neurological, cardiac, gastroenterological, and neuro-ophthalmological involvement. Those considered affected were provided with multidisciplinary treatment and a follow-up. Results As a result of a 7-year selective screening program among the high-risk patient population and relatives of genetically verified affected individuals, 340 carriers of TTR mutations were identified in Bulgaria with the following gene defects: 78.53% with Glu89Gln, 10.29% with Val30Met, 8.24% with Ser77Phe, 2.06% with Gly47Glu, and 0.59% with Ser52Pro. All of these affected displayed a mixed phenotype with variable ages at onset and rate of progression, according to their mutation. From the 150 patients treated with TTR stabilizer, 84 remained stable, while in other 66 patients the treatment was terminated either because of polyneuropathy progression or due to death. A program for a regular follow-up of asymptomatic carriers in the last 3 years enabled us to detect the transition of 39/65 to symptomatic patients and to initiate treatment in a timely manner. Conclusion Bulgarian ATTRv patients display a mixed phenotype with some clinical peculiarities for each mutation that should be considered when treating the affected and the follow-up of the asymptomatic carriers of a specific gene defect.